Motor induced syncope after cerebral infarction: A case report and literature review - Zihan Zhao; Ranran Wang; Lihua Gao; Meijing Zhang (SAGE Open Medical Case Reports)
Cardio-cerebral syndrome refers to cardiac injury following cranial brain injury, representing a critical complication of stroke associated with high morbidity and mortality. Although exercise treadmill testing is widely utilized for myocardial ischemia evaluation, its role in unmasking neurogenic syncope or cardio-cerebral interactions remains under investigation. Existing literature emphasizes that only a small proportion of post-stroke syncope cases undergo comprehensive assessment for combined cerebrovascular–cardiac etiologies, particularly evident in slow-type arrhythmia cases frequently misattributed solely to vasovagal syncope despite potential contributions from brainstem injury or autonomic dysregulation. While most reported post-exercise syncope cases attribute symptoms to vasovagal syncope or common etiologies, underlying cardiovascular/cerebrovascular pathologies are often overlooked, with limited discussion on post-exercise arrhythmia–cerebrovascular disease associations. This report details a unique case of exercise treadmill testing-induced syncope characterized by Brady arrhythmic electrocardiographic changes. Syncope evaluation revealed a newly diagnosed pontine infarction, while cardiac workup excluded structural heart disease, coronary artery stenosis, and Brugada syndrome, underscoring the differential diagnosis challenge between neurogenic and cardiogenic syncope. This case uniquely demonstrates the mechanistic overlap between vasovagal syncope and cerebrovascular injury: although bradyarrhythmia during exercise treadmill testing is typically attributed to cardioinhibitory vasovagal syncope, concurrent pontine infarction likely disrupted brainstem cardio-regulatory centers, sensitizing the patient to vagal hyperactivity. Through systematic analysis of specific arrhythmia–cerebrovascular disease relationships, the final diagnosis identified vasovagal syncope as the primary cause, with cerebral infarction serving as a potential exacerbating factor. This exercise-induced vasovagal syncope complicating stroke provides clinical insights into recognizing overlapping neurovascular–cardiovascular mechanisms during syncope evaluation.